Characterization of the complete chloroplast genome of Saussurea involuerata (Compositae), an endangered species endemic to China. Issue 1 (2nd January 2020) - Wang, Rui; Liu, Jinfeng; Liu, Siyan; Guan, Shuyan; Jiao, Peng
Abstract: Saussurea involuerata (S. involuerata), a kind of composite and perennial herbage plant, is a rare and precious alpine medicinal plants with high medicinal value, it can regulate human's body and has health care function, therefore attracts attention of many scholars. It is currently on the International Union for Conservation of Nature (IUCN) red list of threatened species. In this study, we first assembled the complete chloroplast (cp) genome of S. involucrata by Illumina paired-end reads data. The whole genome was 152, 490 bp, consisting of a pair of inverted repeats of 69, 041 bp, large and small single-copy regions of 69, 045bp and 18, 638 bp in length, respectively. The cp genome contained 134 genes, including 90 protein-coding genes, 36 tRNA genes, and 8 rRNA genes. The overall GC content of the whole genome was 37.7%. A neighbor-joining phylogenetic analysis demonstrated a close relationship between S. involuerata and Arctium lappa .